2017
DOI: 10.1016/j.cemconres.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A new model for the C-S-H phase formed during the hydration of Portland cements

Abstract: 4A model is developed to explain why the C-S-H phase that grows during the hydration of Portland 5Cements initially requires a high water content, much of which is lost by gentle drying. It is proposed 6 that the rapid growth of C-S-H during the hydration of alite (C3S)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(82 citation statements)
references
References 35 publications
3
73
0
6
Order By: Relevance
“…One way to reconcile all of the observations is to suppose that the microstructure of the C-S-H gel, arising from the hydration of alite, is a fine intermixing of tobermorite with amorphous Ca(OH) 2 plus the water in the small and large gel pores [6,13,16]. An updated mechanism of growth of the C-S-H gel, and consequently, the evolution and nature of the gel water, have been very recently proposed [17].…”
Section: Cementsmentioning
confidence: 99%
“…One way to reconcile all of the observations is to suppose that the microstructure of the C-S-H gel, arising from the hydration of alite, is a fine intermixing of tobermorite with amorphous Ca(OH) 2 plus the water in the small and large gel pores [6,13,16]. An updated mechanism of growth of the C-S-H gel, and consequently, the evolution and nature of the gel water, have been very recently proposed [17].…”
Section: Cementsmentioning
confidence: 99%
“…It is in this LD C-S-H that irreversible processes occur during the first drying process. The mechanism can be explained by Gartner, Maruyama, Chen (GMC) model (Gartner et al 2017). The GMC model presumes that dehydration of initially wet C-S-H occurs in discrete steps, in which oxygen atoms associated with water or OH ligands around the charge-balancing Ca cations are replaced by oxygen atoms bound to silicon in the silicate groups attached to the basal CaO layer.…”
Section: Hcpmentioning
confidence: 99%
“…84 represents a reduction of water adsorption sites in the stable C-S-H layers due to drying. This is due to the dehydration of water molecules hydrated with Ca ions on the surface of C-S-H and the generation of Si-O-Ca-O-Si bonds that stabilize the interlayer between mono-C-S-H layers (Gartner et al 2017). This mechanism is considered to be an irreversible process involving C-S-H during the first drying step.…”
Section: Hcpmentioning
confidence: 99%
“…e second major dehydration peak between 400°C and 500°C in each of the DTG curves (Figure 8(b)) was attributed to the decomposition of calcium hydroxide [33]. Tricalcium silicate and dicalcium silicate reacted with water to form C-S-H gels and calcium hydroxide [34]. e intensities of the C-SS and C-GTs paste samples at the curing age of 28 days were stronger than those at the curing age of 3 days, which indicated that the hydration degree was also further deepened with the extension of the curing age.…”
Section: Tg-dtg Analysismentioning
confidence: 99%